Interference of Urochloa decumbens and Panicum maximum in the initial growth of six clones of Eucalyptus urograndis - Colmanetti, Michel Anderson Almeida; Bacha, Allan Lopes [UNESP]; Braga, Andreísa Flores [UNESP]; Alves, Pedro Luis da Costa Aguiar [UNESP]; de Paula, Rinaldo César [UNESP] (Southern Cross Publishing, 2017)
Weeds play a strong pressure on the eucalyptus early growth, leading to a delay in their development. Therefore, many studies have tried to identify eucalyptus clones that are more tolerant to weed competition to supply information to producers, genetic improvement programs and the scientific community. The objective of this study was evaluate the interference of signal grass (Urochloa decumbens) and guinea grass (Panicum maximum) in the early growth of six clones of Eucalyptus urograndis, as well as the reciprocal effect. The experiment was conducted in an open and semi-controlled area in 8-L pots using a completely randomized experimental design with a 3 x 6 factorial scheme (U. decumbens, P. maximum and weed-free control and six eucalyptus clones). After ninety days of planting, the following variables were measured: eucalyptus stem diameter, height, total chlorophyll concentration, chlorophyll fluorescence (Fv/Fm), net assimilation rate and eucalyptus and weed dry biomass. In coexistence with Guinea grass (Panicum maximum), clone 3 (ms 709 H) exhibited a 78.2% reduction in dry biomass compared to clone 4 (C 219 H), which obtained the highest dry biomass. In coexistence with signal grass (Urochloa decumbens), clone 6 (ms 686 H) was the most negatively affected by weed competition, with an 80.7% lower dry biomass than clone 4. In general, clones 1 (ms 710 H), 2 (H 1069) and 4 were more resistant, and clones 3 and 6 were more sensitive to weed interference. Both weeds were affected by eucalyptus, but Guinea grass was more sensitive than signal grass.
Keywords: Competition; Eucalyptus; Guinea grass; Signal grass; Weed management